Public Security and Policy Networks in Brazil - Costa, Arthur Trindade M. (International Journal of Criminology and Sociology, 2018)
This article discussed the problems of governance of the policy networks in Brazilian public security field. After distinguished the concepts of police, policing and policy, we will describe the constitution of public security networks on two issues concerning the residents of Brasilia, the Brazil’s capital: crime-related problems in schools and deaths in the traffic. Then, we will discuss the nature and the challenges of policy networks and evaluate the governance capacity of the Brazilian Secretariats of Public Security (SSP’s). We conclude that there is poor governance capacity due to the historical functions of SSP’s.